2019
DOI: 10.1007/s00044-019-02443-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and anticancer effects of conjugates of doxorubicin and unsaturated fatty acids (LNA and DHA)

Abstract: Doxorubicin (DOX) is a leading cytostatic drug with many adverse effects in use. We are still looking for methods that will allow us to preserve the therapeutic effect against the tumor cells and reduce the toxicity to the normal cells. In our work, we obtained amide derivatives of DOX by reaction of the amino group with α-linolenic (LNA) and docosahexaenoic (DHA) acids (2, 3), as well as double-substituted derivatives via amide and ester linkages (4, 5). The structures of the compounds were confirmed by Proto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Moreover, cytotoxicity level of Dox reported in this work was in the same order of magnitude as the results from other research groups. For instance, after treating the cells with Dox for 24, 48, and 72 hours, the IC 50 values were 65.25 µM (Xu et al, 2003), 0.35 µM (Zhang et al, 2020b) and 0.29 µM (Mielczarek-Puta et al, 2019), respectively. This might indicate that cytotoxicity of Dox increased with the longer treatment durations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, cytotoxicity level of Dox reported in this work was in the same order of magnitude as the results from other research groups. For instance, after treating the cells with Dox for 24, 48, and 72 hours, the IC 50 values were 65.25 µM (Xu et al, 2003), 0.35 µM (Zhang et al, 2020b) and 0.29 µM (Mielczarek-Puta et al, 2019), respectively. This might indicate that cytotoxicity of Dox increased with the longer treatment durations.…”
Section: Discussionmentioning
confidence: 99%
“…A high selectivity index towards cancer cells is an important consideration when assessing the medicinal and therapeutic attributes of bioactive moieties from natural sources. Compounds with high selectivity indices impart lower toxicities to the sensitive and regulated normal proliferative cell compartments in the tissue microenvironment and afford a cost-effective way to rationalize a minimum level of tumor resistance and side effects in response to chemotherapy [15]. Mitochondria play diverse and crucial roles in cell survival and death and are also critical for oncogenesis and the sustained progression of malignant cells.…”
Section: Resultsmentioning
confidence: 99%
“…[25]. Today, studies showed that adjustment of current anticancer drugs by combining these agents with some bioactive compounds can increase the tissue selectivity and may make chemotherapy considerably more effective with lower toxicity [26,27]. In this regard, a number of studies have reported the in vitro and in vivo promising effects of fatty acids which improved the efficacy of the antitumor drugs which enhance the tumor cell targeting selectivity and reduce the cytotoxic effects [25,28].…”
Section: Groupmentioning
confidence: 99%